An Examination of Aishah Abd al-Rahman bint al-Shati’s Approach to Exegesis of The Quran - Saheed Badmus, Suraju; Haleemah Olajumoke, Omotosho (Jurnal Usuluddin, 2023)
In the last few decades, bint al-Shati’s literary approach to exegesis of the Quran has received some scholarly attention being a female exegete of the Quran. Her approach to the interpretation of the Quran shows that her information is hardly from the traditional exegeses. Thus, this paper seeks to examine her various approaches to tafsir to expose her efforts as a modern exegete. Her approaches include but are not limited to the meaning of Quranic words, use of poem, use of conclusion, presentation of the number of times a word appears, use of ilm Qira’at, philological and topical approaches. The paper employed historical and analytical methods of research. The historical method helped in accounting for the biography of bint al-Shati while the analytical method assisted in explaining each of her approaches to tafsir with extracts from her tafsir. The paper revealed that her approach to tafsir is a combination of both traditional and literary study of the Quran with more focus on the former than the latter. It, therefore, concluded that female Muslims should intensify more efforts in the dissemination of Islamic knowledge in a contemporaneous way without neglecting the traditional way.